2011
DOI: 10.1039/c1dt11380a
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic aluminum alkyl complexes as highly active initiators for the polymerization of ε-caprolactone

Abstract: Two dinuclear aluminum alkyl complexes supported by a piperazidine-bridged bis(phenolato) group were prepared, and both complexes exhibited extremely high activity for the ring-opening polymerization of ε-caprolactone. In the presence of benzyl alcohol (BnOH), the polymerization accelerated dramatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 34 publications
(5 reference statements)
4
45
0
Order By: Relevance
“…Multinuclear metal catalysts, such as yttrium, rare earths, group IV, iron, magnesium, copper, zinc, and aluminum have received enormous attention for ROP of cyclic esters. Tolman and co‐workers reported that the polymerization rate for LA with dinuclear zinc catalysts compares favourably to the fastest catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Multinuclear metal catalysts, such as yttrium, rare earths, group IV, iron, magnesium, copper, zinc, and aluminum have received enormous attention for ROP of cyclic esters. Tolman and co‐workers reported that the polymerization rate for LA with dinuclear zinc catalysts compares favourably to the fastest catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…This observation is similar to that reported by Chmura et al 84 for Ti(IV) complexes of bis(phenolate)s, but in contrast to the aluminum systems reported by other authors where less sterically demanding ligands afforded more effective initiators. 85,86 However, by comparing the activity of the methyl complexes with the chloride complexes, the latter showed lower activity and produced polymers with different properties. This trend has also been observed by others.…”
Section: End Group Analysis By 1 H Nmr Spectroscopy and Maldi-tof Masmentioning
confidence: 99%
“…Among the reported initiators, organoaluminum complexes have attracted much attention because they have a good control over the polymerization reaction [7] and low toxicity [8]. However, few studies have involved the alkyl aluminum complexes as the initiator for the ROP of ε-CL without the presence of alcohol, because these complexes usually showed no or very low activity towards this polymerization [9], and most of them got a broad molecular weight distribution during the reaction [9,10].…”
mentioning
confidence: 99%
“…Although plenty of various ligands are employed in the alkyl aluminum initiators [9][10][11], aluminum complexes bearing N,N′-substituted β-diketiminate ("nacnac") ligands and their application in ROP of cyclic esters are still less investigated [10c]. The β-diketiminate ligands have gained increasing interest due to their suitability as fine-tuned spectator ligands by variation of the steric and electronic properties of the N,N′-substituents [12,13].…”
mentioning
confidence: 99%